Desain Extendable Coffee Table dengan fitur Internet of Things (IoT) - Kusumaningrum, Noni; Hutasoit, Nicolas; Prakoso, Galih; Sundara, Gilar (PRODUCTUM Jurnal Desain Produk (Pengetahuan dan Perancangan Produk), 2024)
Coffee table is quite important furniture because it is located in the center of the family room, so the coffee table must appear functionally and aesthetically attractive. Currently, minimalist and multifunctional furniture is growing rapidly with the extendable trend. This research aims to design a coffee table that can be opened lengthwise (extend). The Internet of Things (IoT) feature was added to make it easier to use this coffee table and to follow modern furniture trends. On the other hand, the industrial challenge is an environmentally friendly industry, such as minimizing waste by utilizing leftover materials that can still be used. This research also utilizes industrial wood waste. The coffee table designed in this research can be opened to the side so that it has an additional function as a place to store items. The type of research used is Quantitative Research using the design thinking method as a research method as well as a design method starting with empathy and ending with a test. Both the empathize and test stages use questionnaires as a measuring tool.  The result is that the function and aesthetic value of the extendable coffee table is quite good in terms of size, scale, proportion, texture, pattern and color because it uses appropriate finishing materials. The application of IoT in the design of an extendable coffee table shows that this product can follow technological trends in furniture design in the future and make it easier for users to operate furniture in storage functions without having to use a lot of manual effort.